Polythiophene/graphene/zinc tungstate nanocomposite: Synthesis, characterization, DC electrical conductivity and cigarette smoke sensing application. Issue 6 (July 2021) - Husain, Ahmad; Ahmad, Sharique; Mohammad, Faiz
Herein, we are reporting the synthesis and characterization of polythiophene (PTh) and its novel nanocomposites with zinc tungstate (ZT) and graphene/zinc tungstate (G/ZT) hybrid for Direct current (DC) electrical conductivity based cigarette smoke sensing at room temperature. X-ray diffraction, Fourier-transform infrared, Raman, scanning electron microscopy, transmission electron microscopy, ultraviolet–visible spectroscopy and thermogravimetric analysis techniques were used for the characterization of the as-prepared materials. The results showed that the DC electrical conductivity and sensing performance of PTh significantly improved by incorporation of ZT and G/ZT into it. PTh/G/ZT-3 (i.e. PTh/G/ZT nanocomposite containing 15 wt% G/ZT) was found to be the best sensor in terms of sensing response (81.5%) and reversibility (90.55%) along with the most stable semiconductor under isothermal and cyclic ageing conditions. Sensing response of PTh/G/ZT-3 was also tested in the exposure to various components of cigarette smoke (namely ammonia, carbon dioxide, ethanol, formaldehyde, acetone, benzene, toluene, phenol) and the highest sensing response was observed in the exposure to ammonia. The significant increase in conductivity of PTh/G/ZT nanocomposites was explained by the transfer of polarons from PTh to graphene, that is, creation of a hole in graphene where they achieved rapid mobility along with the extended π-conjugated system. Finally, a sensing mechanism was proposed through adsorption–desorption of cigarette smoke on the surface of PTh/G/ZT where electronic interactions between polarons of PTh and various components of cigarette smoke (mainly ammonia and ethanol) affected the change in DC electrical conductivity.